Histopathological spectrum of spindle cell tumours of gastro-intestinal tract - Rasool, Zubaida; Feroz, Imza; Wani, Abdul Haseeb; Nazir, Mir Wajahat un (International Journal of Advances in Medicine, 2019)
Background: Spindle cell lesions of gastro-intestinal tract (GIT) are relatively uncommon tumours compared to epithelial tumours. The anatomic location of spindle cell tumour is important, whether the tumour is located in mucosa, submucosa or muscularis propria. Methods: Authors endeavoured to study the histopathological spectrum of spindle cell lesions for a period of one year from January 2018 to December 2018 in our hospital. Results: This was a prospective study of 1 year starting from January 2018 to December 2018. A total of 30 cases of spindle cell lesions of gastrointestinal tract were seen. Out of 30 cases 23 were gastrointestinal stromal tumours (GIST), 2 cases were schwannomas, 2 cases were of leiomyomas, 1 case was fibromatosis, 1 case was inflammatory fibroid polyp, and one case was inflammatory myofibroblast tumour. Conclusion: GISTs are the commonest spindle cell tumours of GIT. Besides GIST, there are other spindle cell tumours which range from benign to malignant, and need to be differentiated from GIST for proper management.